Mapeamento de competências de gestores da atenção em saúde pública em municípios de região de fronteira - Hortelan, Michele dos Santos (2019)
The managers of the Unified Health System (SUS), are also part of public health and act directly and indirectly in health care, we can thus conceptualize health management as the ability to deal with disagreements, suggest methods, protocols, reference indicators for analyze the actions of the health teams. Brazil is an atypical territory, since it borders almost all the countries of South America, however, the countries bordering Brazil do not have a free health system such as SUS. The objective of this research is to map the competencies of public health managers who work in border cities in a border region. This is an exploratory descriptive research of a quantitative approach for mapping the essential competences of managers in public health in the neighboring municipalities of the border region. Fisher's exact non-parametric test was used, a significance level with p-value less than or equal to 0.05 was considered, being performed in program R. The research counted on the participation of 12 municipalities where 62 managers of public health answered the questionnaire in its entirety, the documentary analysis of the work used the law 8080/90 and the National Policy of Basic Attention of 2017 as bases to identify the necessary competencies for the manager, regarding the characterization of the participants there was predominance of sex (87.09%) who had specialization (51.61%) and are nurses (58.06%). The analysis of bivariables showed a greater proportion of men who claim to be more competent even though the minority, with regard to the level of schooling, it was found that the higher the level of schooling, the more competencies they present, and thus those with a master's degree and PhD. Competence mapping identified two knowledge gaps in domain 2 "Surveillance and damage control" and 6 "Global and international health". It is concluded that the gap found in the mapping is closely related to the border region, since it is a place where people can easily transit from one border to another is perceptible to the difficulty of controlling risks and damages to the disease, regarding global health, Brazil does not have binational partnerships with border countries that formalize service agreements with one another.